A visual journey through man's lifetime on Earth - "Brooks, Philip" (Ladybird: Loughborough, 1997)
Covering history and prehistory over the last 12,000 years - thinking, building, fighting wars, and the arts - this book is geared towards eight to ten-year-olds. It includes a special fold-out feature, "The Big Bang to the Present Day".
Keywords: General History - Book